Specific Characteristics of Pedagogical Education Innovation Cluster - Sobirjonovna, Kadirova Omadkhan; Abdullaeva, Nasiba (Research Parks Publishers, 2023)
In this article, the reforms carried out in pedagogical education in our country today are aimed at strengthening the position of the teaching profession in society, attracting advanced foreign experiences and innovations to the field, ensuring the integration of education, science, production, and the main aspects of education. and improvement of auxiliary tools in accordance with the times, more involvement of the private sector in the field and improvement of the system of working with gifted students.